Improved magnetic regulation of delivery profiles from ferrogels. (April 2018) - Kennedy, Stephen; Roco, Charles; Déléris, Alizée; Spoerri, Patrizia; Cezar, Christine; Weaver, James; Vandenburgh, Herman; Mooney, David
Abstract: While providing the ability to magnetically enhance delivery rates, ferrogels have not been able to produce the various types of regulated delivery profiles likely needed to direct complex biological processes. For example, magnetically triggered release after prolonged periods of payload retention have not been demonstrated and little has been accomplished towards remotely controlling release rate through alterations in the magnetic signal. Also, strategies do not exist for magnetically coordinating multi-drug sequences. The purpose of this study was to develop these capabilities through improved ferrogel design and investigating how alterations in the magnetic signal impact release characteristics. Results show that delivery rate can be remotely regulated using the frequency of magnetic stimulation. When using an optimized biphasic ferrogel design, stimulation at optimized frequencies enabled magnetically triggered deliveries after a delay of 5 days that were 690- to 1950-fold higher than unstimulated baseline values. Also, a sequence of two payloads was produced by allowing one payload to initially diffuse out of the ferrogel, followed by magnetically triggered release of a different payload on day 5. Finally, it was demonstrated that two payloads could be sequentially triggered for release by first stimulating at a frequency tuned to preferentially release one payload (after 24 h), followed by stimulation at a different frequency tuned to preferentially release the other payload (After 4 days). The strategies developed here may expand the utility of ferrogels in clinical scenarios where the timing and sequence of biological events can be tuned to optimize therapeutic outcome. Graphical abstract: